2016
DOI: 10.1136/neurintsurg-2016-012730
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative flow measurement after placing a flow diverter for a distal internal carotid artery aneurysm

Abstract: Without using extra contrast medium or radiation dosages, color-coded DSA enables quantitative monitoring of the cerebral circulation after flow-diverting treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…Intuitively, distal intracranial hemodynamics are likely altered after PED deployment but these changes are still poorly understood. [14][15][16][17] Moreover, whether these hemodynamic changes can lead to DIPH is unknown. DIPH is an unexpected and devastating complication, with an incidence ranging from 0% to 10% among reported series.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intuitively, distal intracranial hemodynamics are likely altered after PED deployment but these changes are still poorly understood. [14][15][16][17] Moreover, whether these hemodynamic changes can lead to DIPH is unknown. DIPH is an unexpected and devastating complication, with an incidence ranging from 0% to 10% among reported series.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] Multiple etiologies and mechanisms have been proposed, [4][5][6][7][8][9][10][11][12][13][14] including disrupted cerebral hemodynamics, 5,6,8,11,[13][14][15][16][17] but no mechanism has been definitively proven. [4][5][6][7][8][9][10][11][12][13][14][15][16][17] Here, we evaluate short-and long-term intracranial hemodynamic changes following PED deployment by analyzing contrast transit times on DSA using syngo iFlow software. We found that MCA to ICA transit time ratio decreased immediately after treatment (1.13 vs. 1.22, p < 0.01), corroborating the results of faster blood flow in the distal circulation following PED deployment published in previous studies conducted with syngo iFlow analysis, 17 quantitative magnetic resonance angiography (MRA), 14 and transcranial Doppler.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] Color-coded and quantitative digital subtraction angiography (QDSA) is a technique that uses the syngo iFlow (Siemens, Munich, Germany) software to post-process the data, utilizing all of the images in a given DSA sequence to generate a color map that displays the maximum opacification time and provides time-intensity curves and quantitative flow measurements for a given point or region of interest (ROI). [7]…”
Section: Introductionmentioning
confidence: 99%
“…While some QDSA studies have been published, no such study has quantified HCCs in comparison with the background cirrhotic liver. [79] The purpose of this study was to report our early experience using color-coded QDSA for perfusion quantification and time-intensity curve evaluation of HCCs, as well as the background cirrhotic liver.…”
Section: Introductionmentioning
confidence: 99%